2010
DOI: 10.1002/atr.136
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid model for prediction of bus arrival times at next station

Abstract: SUMMARYEffective prediction of bus arrival times is important to advanced traveler information systems (ATIS). Here a hybrid model, based on support vector machine (SVM) and Kalman filtering technique, is presented to predict bus arrival times. In the model, the SVM model predicts the baseline travel times on the basic of historical trips occurring data at given time-of-day, weather conditions, route segment, the travel times on the current segment, and the latest travel times on the predicted segment; the Kal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 22 publications
1
76
0
1
Order By: Relevance
“…They compared the performance of these two models and found both had their own advantages. Similar to Chien's et al (2000) study, Yu et al (2010) presented a hybrid model and found his model generally provides better performance than conventional ANN method. More recently, Lin et al (2013) and Khetarpaul et al (2015) proposed hybrid arrival time prediction models combining ANN and clustering methods to capture the traffic fluctuations and determine the parameter inputs of different clusters more clearly.…”
Section: Literaturesupporting
confidence: 60%
See 2 more Smart Citations
“…They compared the performance of these two models and found both had their own advantages. Similar to Chien's et al (2000) study, Yu et al (2010) presented a hybrid model and found his model generally provides better performance than conventional ANN method. More recently, Lin et al (2013) and Khetarpaul et al (2015) proposed hybrid arrival time prediction models combining ANN and clustering methods to capture the traffic fluctuations and determine the parameter inputs of different clusters more clearly.…”
Section: Literaturesupporting
confidence: 60%
“…The previous studies also prove that situation 1 is more popular (Shalaby, Farhan 2004;Zheng et al 2012;Yu et al 2006Yu et al , 2010Yu et al , 2011. However, situation 2 has two unique advantages:…”
Section: Detection Point Standardizationmentioning
confidence: 79%
See 1 more Smart Citation
“…SVM was developed by Vapnik [14,15], which is characterized by a specific type of learning algorithms. It has been successfully applied to solve some classic problems, such as incident detection [16], traffic-pattern recognition [17], passenger head recognition [18], and travel time prediction [7,8,[19][20][21]. SVM is used to find regular pattern and makes use of them to analyse the unknowns.…”
Section: S Zhong Et Al: a Hybrid Model Based On Support Vector Machmentioning
confidence: 99%
“…According to statistics on Beijing's business zones, the average radius of such a zone is approximately 1 km. The average riding time for a trip by bus or subway from a parking location outside a business zone to a travel destination in the business zone was calculated as 8.00 min for parking during peak hours and 6.00 min for parking during off-peak hours based on the Beijing parking survey data [36][37][38][39]. In addition, according to the parking survey data, the average walking time (from the parking location to the destination) after parking in a business zone is approximately 3.14 min, and the average time required to walk from outside a business zone to a travel destination in the business zone was set at 8.00 min [40][41][42].…”
Section: Wang Fujingmentioning
confidence: 99%